Isolated Spherophakia and Glaucoma - Joseph Pikkel; Epstein Irena (Case Reports in Medicine)
We report a case of spherophakia that caused glaucoma and describe the characteristics and the ultrasound biomicroscopy findings as well as the mechanism and management of glaucoma in spherophakia. We suggest considering lens extraction to manage glaucoma in spherophakia and discuss the surgical considerations and possible complications of such an intervention.